Pengaruh User Generated Content dan Brand Love terhadap Keputusan Pembelian (Studi pada Konsumen Produk Ms Glow di Kota Medan): Penelitian - Rizqa Nabilah Rangkuti; Ainun Mardhiyah; Onan Marakali Siregar; Kartini Harahap (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze the influence of User Generated Content (UGC) and Brand Love on the purchase decisions of Ms Glow product consumers in Medan City. Motivated by the significant growth of the Indonesian beauty industry post-pandemic, where the self-care segment dominates the market, this quantitative study with an associative approach examines the partial and simultaneous effects of both variables through multiple linear regression analysis, following the verification of classical assumptions (normality, multicollinearity, and heteroscedasticity). The results indicate that UGC and Brand Love significantly impact the purchase decisions of Ms Glow consumers. This is supported by a correlation coefficient (R) of 0.777, indicating a strong relationship between the variables, and an Adjusted R Square value of 0.596, meaning that 59.6% of the variance in purchase decisions can be explained by UGC and Brand Love. Furthermore, the majority of respondents showed a positive perception of Ms Glow, particularly regarding customer involvement in product promotion and the emotional connection with the brand. These findings provide empirical insights into the crucial role of UGC and Brand Love in shaping consumer purchase decisions within the context of beauty products in Medan City.